First report of the family Attevidae (Lepidoptera, Yponomeutoidea) from Cambodia, with description of a new species - Na, Sol-Moon; Bae, Yang-Seop (Zootaxa, 2024)
In the present study, we report a pantropical family Attevidae of the superfamily Yponomeutoidea in Cambodia for the first time. A new species, Atteva chalco sp. nov., and two newly recorded species, A. fabriciella Swederus, 1787, A. wallengreni Sohn and Wu, 2013 are reported. Illustrations of adults, male and female genitalia, diagnoses, and descriptions are provided.